Terorisme: Perspektif Barat dan Islam - Hefzan, Mohd.; Fitria, Fitria (Sisi Lain Realita, 2017)
The issue of terrorism has tapped the border of human civilization. The West has a view on terrorism following their own perceptions. Now the Western world is afraid of their own shadows after the entry into force of the events of September 11, 2001 which have embodied the World Trade Center (WTC) in New York. This black event has really shocked the Western world which so far they are proud that the United States is the great power of the world, has now been attacked so extreme. The problem that arises now in the Islamic world is that the West has misinterpreted what is said to be jihad. The enemy of Islam has labeled terrorism as a jihad in Islam, this is how the West tries to put Islam as a ferocious religion. The term jihad is what terrorism says for the West. In Islamic teachings jihad cases are something that is highly demanded and has no direct connection with terrorism activities.